Emergence of Community-Genotype Methicillin-Resistant Staphylococcus aureus in Korean Hospitals: Clinical Characteristics of Nosocomial Infections by Community-Genotype Strain - Joo, Eun-Jeong; Chung, Doo Ryeon; Kim, So Hyun; Baek, Jin Yang; Lee, Nam Yong; Cho, Sun Young; Ha, Young Eun; Kang, Cheol-In; Peck, Kyong Ran; Song, Jae-Hoon (Infection & chemotherapy, 2017)
As community-genotype methicillin-resistant Staphylococcus aureus (MRSA) strains spread into hospitals, the genotypes of the MRSA strains causing hospital-acquired (HA) infections have become more diverse. We describe clinical characteristics of nosocomial MRSA infections by a community-genotype of sequence type (ST) 72. A case-control study was designed among patients with HA-MRSA infections. Forty patients with infections caused by ST72-MRSA SCCmec type IV were selected as cases. Cases were matched to the controls with 106 patients infected with ST5/ST239 MRSA, which are representative hospital genotypes in Korea. Patients infected with ST72 isolates were younger than those with ST5/ST239 isolates. Female gender predominated among ST72 MRSA group compared to ST5/ST239 MRSA group. Solid tumor was a more frequent underlying disease in MRSA infections by ST72 isolates, whereas underlying renal, lung, heart, and neurologic diseases were more frequently found in those by ST5/ST239 isolates. The most common type of infection was pneumonia in both ST72 and ST5/ST239 groups (45.0% vs. 51.9%), followed by skin and soft tissue infection (SSTI). Female gender and underlying solid tumor were identified to be independent predictors for MRSA infections by ST72 isolates. All-cause mortality rates (20.0% vs. 30.2%) were not different between the groups. A community-genotype MRSA, ST72 isolate has emerged as a nosocomial pathogen presenting as hospital-acquired pneumonia and SSTI. Although differences in underlying disorders were found, the distribution of infection type and mortality rate did not differ between the groups.